Leuit Badui: Simbol Estetika, Ketahanan Pangan, dan Religi - Hakiki, Kiki (Societas Dei: Jurnal Agama dan Masyarakat, 2025)
This article examines leuit as a symbol of aesthetics, food security, and spirituality in Badui community in Banten. This research is motivated by the need to explore the multifunctional role of leuit in the cultural and daily life of the Badui community in depth. The main objective of this research is to analyze how leuit functions not only as a granary, but also as an aesthetic representation and center of spirituality. The methodology used includes a qualitative approach through direct observation, in-depth interviews, and literature study to obtain comprehensive data. The results show that leuit has an important role in the food security of Badui community through sustainable and efficient storage. In addition, leuit also contains deep spiritual meaning and serves as a symbol of Badui cultural identity. This research underscores the importance of leuit preservation as part of the cultural heritage that supports the sustainability of the Badui community and provides insight into the contribution of traditional cultural practices in facing global challenges.